Party politics in semi-democracies : a comparative study of Bangladesh and Malaysia - Hasan, Moyenul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Political parties are crucial actors in representative democracy. Bangladesh and Malaysia are two democratic countries in Asia with a common British colonial heritage. This study analyzes and compares the party systems in the two countries based on their practice of semi-democracy in contemporary politics. This study has adopted an institutional approach to analyzing party politics in Bangladesh and Malaysia. It has used qualitative data analysis involving description and explanation of important factors, characteristics and tendencies of certain political parties. Based on data collected from secondary sources the research has identified similarities and differences among the political parties in the areas of regularity in party election, decision-making process and frequency in leadership change as well as mode, issues and methods of interactions. The research has found that both Bangladesh and Malaysia have maintained vibrant party systems throughout their history, though in the case of Bangladesh party politics have experienced military constraints for about a decade. Comparatively, Malaysian political parties maintain a better profile compared to their counterparts in Bangladesh. In terms of frequency in leadership change, the three older political parties in Malaysia have relatively frequent and regular leadership changes compared to the three Bangladeshi parties which have maintained very poor record. However, with regards to decision making and party elections, the political parties in Bangladesh and Malaysia similar to each other, though the three political parties in Bangladesh are more dictatorial in decision-making and in keeping party elections at bay. Malaysian parties have the tendency of maintaining regularity in elections even though there are alleged manipulations in the process. In terms of internal party democracy, Bangladeshi parties perform poorly compared to the Malaysian ones. The level of tolerance, cooperation and coexistence is very low in the case of Bangladeshi political parties, while these are more solid in the case of Malaysian political parties. Finally, the ruling parties in both countries have resorted to legal means to suppress the opposition, especially targeting its leaders. A one party dictatorial rule has become a political norm in Bangladesh. In Malaysia too it is apparent that the ruling BN has resorted to legal means to tame the influential opposition leaders. However, at the end party institutionalization and inter-party systemic interactions in Malaysia are apparently more stable, formal and non-violent compared with Bangladeshi political parties.